Establishment of RpHluorin2-expressing cell and its application in monitoring JTC-801-induced alkaliptosis via multi-dimensional fluorescence detection approaches - Guo, Jie; Mai, Feng-Yi; Li, Xin-Yu; Liang, Jing-Rong; Yang, Wen-Tao; Li, Chen-Guang (Frontiers in Cell and Developmental Biology, 2025)
Dysregulation of intracellular pH (pHi) is a hallmark biological feature of cancer cells, which hijack pHi homeostasis to sustain malignant phenotypes including uncontrolled proliferation, invasion, and metabolic reprogramming. Meanwhile, alkaliptosis, a newly defined pH-dependent form of regulated cell death specifically triggered by the small-molecule compound JTC-801, has emerged as a promising therapeutic target for cancer intervention. However, reliable tools for monitoring dynamic pHi changes during alkaliptosis remain insufficient. RpHluorin2 is an optimized ratiometric pH-sensitive green fluorescent protein variant with enhanced fluorescence intensity and stability. Herein, we established a stable RpHluorin2-expressing cell line and further developed a multi-dimensional fluorescence detection workflow, which encompasses a microplate reader, fluorescence microscopy, flow cytometry, a small animal imaging system (IVIS Spectrum), and a protein dot blot assay coupled with IVIS. Our results demonstrated a strong linear correlation between RpHluorin2 fluorescence intensity and cell number, with a coefficient of determination (R2) of 0.9998. Furthermore, across all employed detection methods, JTC-801 treatment induced dose-dependent and time-dependent reductions in RpHluorin2 fluorescence, an observation that is consistent with the elevation of pHi during alkaliptosis. This platform enables high-throughput screening, single-cell analysis, and biochemical validation, providing a robust tool for mechanistic research on alkaliptosis and the development of pH-targeted anticancer therapies.